Mechanisms of photobiomodulation therapy in treating and preventing antineoplastic-induced oral mucositis: a systematic review - Paulo Victor Alves de Sales; Isabella Piassi Dias Godói; Gerly Anne de Castro Brito; Renata Carvalho Leitão; Aurigena Antunes de Araújo; Caroline Addison Carvalho Xavier de Medeiros (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To conduct a systematic review of the mechanisms of photobiomodulation therapy (PBMT) for treating or preventing oral mucositis (OM) caused by antineoplastic therapy. Methods: Following PRISMA 2020 guidelines, a search was conducted in Medline, Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), and Bibliografia Brasileira de Odontologia from August to September 2023 using descriptors related to OM and laser therapy. Studies on the mechanisms of photobiomodulation in OM were included. Randomized (RCTs) or non-randomized trials from the past 10 years were reviewed. Risk of bias was assessed using RoB 2.0 and ROBINS-I tools. Results: A total of 355 studies was identified. After the screening, seven met the eligibility criteria. The RCTs showed a low risk of bias. PBMT reduced OM incidence in patients undergoing chemotherapy/radiotherapy. PBMT decreased pro-inflammatory cytokines (interleukin-6, tumor necrosis factor-α) and increased anti-inflammatory cytokines (interleukin-4, interleukin-10). It also modulated inflammatory mediators, enhancing the antioxidant enzyme superoxide dismutase and overexpressing genes for keratinocyte differentiation, aiding injury repair. Conclusion: The findings suggested that the mechanism of action of PBMT in OM involves modulation of the inflammatory response, balancing oxygen reactive species generation, and expression of factors related to healing or repair. Further studies are needed to elucidate these mechanisms and optimize treatment protocols.